Antibacterial Activity of Papaya Seeds (Carica papaya L.) Ethanol Extract Against Escherichia coli - Eliya Mursyida; Fitria Dina Sella; Deinike Wanita Marwan (Sistem Informasi, 2022)
Escherichia coli is a normal flora found in the large intestine of humans and is opportunistic. Acute diarrhea is the discharge of watery or loose stools in larger amounts than normal, lasting less than 14 days. Acute diarrhea is caused by several microbes, one of which is Escherichia coli. Treatment of acute diarrhea caused by bacteria can be given antibiotics, but the relatively high use of antibiotics can lead to resistance. One of the natural ingredients known to treat acute diarrhea is papaya seeds (Carica papaya L.). Papaya seeds are known to have antibacterial activity because they contain flavonoids (quercetin), alkaloids, saponins, and tannins. This study aims to determine and analyze the antibacterial activity of the ethanol extract of papaya seeds on the growth of Escherichia coli. This research is an experimental study with a post-test only with a control group research design using papaya seeds (Carica papaya L.). The test bacteria used in this study were Escherichia coli with the dilution method to determine the Minimum Inhibitory Concentration (MIC) and the spread plate to determine the Minimum Bactericidal Concentration (MBC). The results showed that MIC was present at a concentration of 2%, while MBC was at a concentration of 5%. It was concluded that the ethanol extract of papaya seeds (Carica papaya L.) had antibacterial activity against Escherichia coli.